Diagnostic agreement among experts assessing adults presenting with possible cystic fibrosis: need for improvement and implications for patient care. Issue 4 (12th December 2022) - Franciosi, Alessandro N.; Tanzler, April; Goodwin, Jodi; Wilcox, Pearce G.; Solomon, George M.; Faro, Albert; McElvaney, Noel G.; Downey, Damian G.; Quon, Bradley S.
Background: Increasing awareness of milder presentations of cystic fibrosis (CF) and greater interest in non-CF bronchiectasis are likely to lead to more CF screening by respiratory clinicians. As a result, adults who may not strictly fulfil CF diagnostic criteria yet display evidence of abnormal CF transmembrane conductance regulator (CFTR) function are being identified. The degree of agreement on diagnosis and care needs in these cases between CF clinicians remains unknown, and has implications for patient care, including access to CFTR modulator therapies. Methods: We surveyed adult CF physicians in Canada, the USA, the UK and Ireland, and presented them with anonymised vignettes of adult patients referred for assessment of possible CF. Diagnostic inter-rater agreement over diagnosis, ease of classifying cases and appropriate follow-up was assessed using Krippendorff's reliability coefficient (α). Results: Agreement over diagnosis (α=0.282), ease of classification (α= −0.01) and recommended follow-up (α=0.054) was weak. Clinician experience (>10 and 5–10 years versus <5 years) and location (UK and Ireland versus Canada) were associated with higher odds of recommending further testing compared with selecting a formal diagnosis (respectively, OR 2.87; p=0.022, OR 3.74; p=0.013 and OR 3.16; p=0.007). A modified standard of care was recommended in 28.7% of cases labelled as CF. 70% of respondents agreed with the statement that "Accurate distinction between CF and CFTR-related disorder has become significantly more pertinent with the advent of highly effective CFTR modulators". Conclusions: Our results demonstrate low diagnostic concordance among CF specialists assessing cases of possible adult CF and highlight an area in need of improvement. Adult presentations of possible CF present a major diagnostic challenge and agreement on diagnosis is unsatisfactory. This is an area in need of significant improvement, and has potential consequences for patient experience and access to specialised care. https://bit.ly/3PhpnKc